Studying the Effect of Titania Additions on some properties of Porcelain - Abbas K. Saadon (Al-Mustansiriyah Journal of Science)
The paper presents the production of porcelain for the ceramic by inexpensive natural raw materi-als, the principal raw materials of porcelain composition was selected consisting of 50% kaolin, 25% feldspar, 25% silica, the sample synthesized were characterize by X-ray diffraction (XRD) technique, than study the effect additives at different concentration form titanium oxide (𝑇𝑖𝑂2 )at (2, 5, 10, 15, 20) wt% on some physical and dielectric properties of porcelain. The samples are prepared by the conventional manufacturing method. The physical and dielectric properties of porcelain show that change considerably with the sub-stituent sample. It was found that the increase of the titanium oxide (𝑇𝑖𝑂2 ) additives of all our sample produce increasing in dielectric constant and bulk density, while decreasing with open porosity and dielectric loss tangent.